Targeted 64Cu-labeled gold nanoparticles for dual imaging with positron emission tomography and optical imaging - Pretze, Marc; Meulen, Nick P. van der; Wängler, Carmen; Schibli, Roger; Wängler, Björn (Journal of labelled compounds and radiopharmaceuticals, 2019)
Gold nanoparticles (AuNPs) have been used for many years in cancer treatment mainly for brachytherapy, but in the last 15 years, the focus has shifted to the development of ultrasmall target-specific AuNPs with homogeneous size and, ultimately, tailored shapes for use in various imaging modalities such as computed tomography (CT), Raman, or photoacoustic imaging. Here, we report on the development of tumor-specific AuNPs as diagnostic tools intended for the dual detection of prostate cancer via optical imaging (OI) and positron emission tomography (PET). The AuNPs were decorated with a near-infrared dye and NODAGA chelator for complexation with radiometals. Radiolabeling with 64Cu was performed either indirect by complexation with NODAGA-AuNPs or by direct reduction of [64Cu]Cu(0) onto the surface of the AuNPs. Both methods yielded stable 64Cu-AuNPs with radiochemical yield more than 95% confirmed by HPLC. 64Cu-AuNPs were evaluated in a dual-imaging setting in vitro and in vivo and exhibited favorable diagnostic properties concerning detection, biodistribution, and clearance. Furthermore, the first therapeutic properties of the 64Cu-AuNPs were evaluated in vitro concerning acute and long-term toxicity, indicating that these 64Cu-AuNPs could be used in therapeutic concepts in the future.
Im Titel ist die Zahl "64" hochgestellt
Gesehen am 03.04.2020